Growth enhancement of tissue culture banana plantlets with proper shading technique at poly-bag stage - Venkat Kanagasingam (2016)
Musa acuminata; fondly known as the Cavendish banana is constantly at high demand. Hence there is a need to increasing the production of this crop and one of the ways is through tissue culture technique. To allow better hardening environment, different shading height and shading layers were manipulated to study on the enhancement of the tissue culture plantlets of Musa acuminate. From this study the recommended shading height for taller crop height and thicker girth size is 50cm for with single layer of shading at the top and the side. This indicates that 50cm of shading height incorporated with single shading layers at the top and the side of the plantlet for optimum for better growth of tissue culture plantlets of Musa acuminata.